Insights on glucocorticoid receptor activity modulation through the binding of rigid steroids - Presman, D.M. (2010)
Background: The glucocorticoid receptor (GR) is a transcription factor that regulates gene expression in a ligand-dependent fashion. This modular protein is one of the major pharmacological targets due to its involvement in both cause and treatment of many human diseases. Intense efforts have been made to get information about the molecular basis of GR activity. Methodology/Principal Findings: Here, the behavior of four GR-ligand complexes with different glucocorticoid and antiglucocorticoid properties were evaluated. The ability of GR-ligand complexes to oligomerize in vivo was analyzed by performing the novel Number and Brightness assay. Results showed that most of GR molecules form homodimers inside the nucleus upon ligand binding. Additionally, in vitro GR-DNA binding analyses suggest that ligand structure modulates GRDNA interaction dynamics rather than the receptor's ability to bind DNA. On the other hand, by coimmunoprecipitation studies we evaluated the in vivo interaction between the transcriptional intermediary factor 2 (TIF2) coactivator and different GR-ligand complexes. No correlation was found between GR intranuclear distribution, cofactor recruitment and the homodimerization process. Finally, Molecular determinants that support the observed experimental GR LBD-ligand/TIF2 interaction were found by Molecular Dynamics simulation. Conclusions/Significance: The data presented here sustain the idea that in vivo GR homodimerization inside the nucleus can be achieved in a DNA-independent fashion, without ruling out a dependent pathway as well. Moreover, since at least one GR-ligand complex is able to induce homodimer formation while preventing TIF2 coactivator interaction, results suggest that these two events might be independent from each other. Finally, 21-hydroxy-6,19-epoxyprogesterone arises as a selective glucocorticoid with potential pharmacological interest. Taking into account that GR homodimerization and cofactor recruitment are considered essential steps in the receptor activation pathway, results presented here contribute to understand how specific ligands influence GR behavior. © 2010 Presman et al.